(3YLGFH GdeNdhbGJs - (3RcQjG Hf eMeO Hf eMehO,GdnbrRphjfj, CHh jMji YeGO GdOjf,J (B682 (3g` s
(3ChdgG (B:s
(3Cfg deG bVi Gddg JYGdi Ydi HYO GdOGQ hGdhWf heaGQbI GdCgd hGdScf CbHdJ Ydi eWGdYI GdcJH s
(3BNQgG (B:s
(3dGjMOK EdGfGOQkG s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B46 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B183s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeYGQa GdYGeIs